Kinematics of soccer dribbling in different tasks - Chang, J.-H.; Lo, T.-Y.; Chang, W.-Y.; Chen, Y. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to find the differences in kinematics between different speeds and cutting directions. Ten male university division 1 soccer players served as the subjects in this study. The Vicon Motion System and the KISTLER force platform were used synchronously to collect data. The length of projection vector was normalized by leg length. 2way ANOVA was used for statistics. Simple main effect was tested if no significant interaction effect was noted. The significant level was set as .05. The length of projection vector between COM and the heel of pivot leg onto X-Y plane in high speed tasks were longer than that in low speed tasks (p < .05). The angle between the X axis and the projection vector between COM and the heel of pivot leg onto X-Y plane had significant interaction effect (p < .05). In low speed tasks, players` pivot legs landed more laterally and that might enhance lateral motion of body, especially when players cut to the dominate side (right). It was concluded that players would change their cutting tactics at different speeds and in different directions. Landing position of pivot leg might be a factor that would help defender to know the cutting side of attacker at low dribbling speed.